A forest‐specialist carnivore in the middle of the desert?Comments on Anabalon et al. 2019. Issue 8 (25th March 2020) - Moreira‐Arce, Darío; Silva‐Rodríguez, Eduardo A.; Napolitano, Constanza; D'Elía, Guillermo; Cabello, Javier; Millán, Javier; Hidalgo‐Hermoso, Ezequiel; Farías, Ariel A.
Abstract: We present comments on an article recently published in Ecology and Evolution ("High‐resolution melting of the cytochrome B gene in fecal DNA: A powerful approach for fox species identification of the Lycalopex genus in Chile") by Anabalon et al. that reported the presence of Darwin's fox ( Lycalopex fulvipes ), a temperate forest specialist, in the hyperarid Atacama Desert of northern Chile. We argue that this putative record lacks ecological support in light of ongoing research on this endangered species, and contains numerous methodological flaws and omissions related to the molecular identification of the species. Based on these issues, we suggest the scientific community and conservation decision‐makers disregard the alleged presence of the Darwin's fox in the Atacama Desert. Abstract : We present a Reply letter for a recent paper reporting the presence of Darwin´s fox, a forest‐specialist canid, in the Atacama Desert, 1, 200 km north of its known distribution.